Peran Literasi Kesehatan Digital dalam Meningkatkan Kesiapsiagaan Masyarakat terhadap Penyakit Kronis - Nanda Pratama Saputra; Dinda Maharani Putri; Fajar Aditya Nugraha Nugraha (Gema Cendekia Institute, 2026)
Abstract Chronic diseases remain one of the leading causes of morbidity and mortality worldwide. The rapid expansion of digital health technologies has increased public access to health information and healthcare services. However, broad access alone does not guarantee the ability to search, understand, evaluate, and apply digital health information effectively. Therefore, digital health literacy has emerged as a critical determinant of preparedness for chronic disease prevention and management. This article aims to analyze the role of digital health literacy in enhancing community preparedness for chronic diseases based on recent empirical evidence. A narrative literature review approach was employed using international scholarly publications published between 2021 and 2025. The analysis focused on studies examining the relationship between digital health literacy, chronic disease self-management, patient activation, utilization of digital health services, and health-related behaviors. The findings indicate that digital health literacy significantly improves individuals' ability to access reliable health information, strengthens self-efficacy, enhances self-management behaviors, increases the utilization of digital health services, and supports informed health decision-making. Furthermore, digital educational interventions have been shown to improve digital health literacy among vulnerable populations, including older adults and individuals living with chronic conditions. These findings suggest that strengthening digital health literacy should become an integral component of health promotion and chronic disease prevention strategies to improve long-term community preparedness.